Profile and Economic Impacts of Agriculture and Natural Resource Industries in the Central Region of Florida - Mohammad Rahmani; Alan W. Hodges; W. David Mulkey (EDIS, 2005)
This report provides a profile of agriculture and natural resource industries and an overview of their economic impacts for a 20-county region in central Florida (Figure 1). Additional reports provide similar information for the northeast, northwest, south, and Suwannee River Basin areas of the state. The report is based on data from the IMPLAN Pro database for Florida counties for 2002 and data from the 2002 Census of Agriculture.